Sundanese Creed of Shahadah: The Relationship between Sundanese Teachings, Culture, and Religion - Supriatna, Wawan; Kuswana, Dadang; Hernawan, Wawan (Jurnal Iman dan Spiritualitas, 2024)
This writing is to find out the creeds have developed in Sundanese society and the dialectical implications of Islam and local culture of this Mantra Creed in Sundanese social and religious life. Meanwhile, the method used is a type of qualitative research or qualitative method of inquiry, namely an in-depth study using data collection techniques directly from people in their natural environment. According to Bogdan and Taylor, qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior. The results of the research found several things, including: First, the shahada in Sundanese society has a broader scope than just aspects of Islam, involving various types of shahada in Sundanese with the aim of incantations for supernatural powers or fulfilling immediate needs, showing circumvention of Islamic law but recognizing Islam as a spiritual teaching. Second, Sundanese people's understanding of the Mantra Creed varies, revealed through analysis of the texts of the Sundanese creed, the Sri Sedana pantun, and the Sundanese version of Martabat Tujuh. Although many people know the text of the Sundanese shahada, only a few understand it in depth. The belief that Sundanese people were already Muslim before the arrival of Islam is confirmed through Pantun Sri Sedana, reflecting acculturation between Sundanese and Islamic teachings. Third, the dialectical implications of Islam and local culture from the shahadah mantra in Sundanese social and religious life include three aspects of Islamic teachings and Sundanese belief system.